ANÁLISE DO PROCESSO DE INSTITUCIONALIZAÇÃO DO TELETRABALHO NA UNIVERSIDADE FEDERAL DA FRONTEIRA SUL (UFFS) CAMPUS LARANJEIRAS DO SUL - SANTOS, KAMILLE MACHADO DOS (2023)
The coronavirus (COVID-19) pandemic has brought about changes in society and advancements in Information and Communication Technology (ICT) in the realm of work. Due to the historical context, there has been a demand for new ways of conducting work through telecommuting or remote work. Telecommuting is characterized by allowing employees to carry out their tasks in diverse environments outside the conventional office. This research addresses the institutionalization of telecommuting at the Federal University of Fronteira Sul (UFFS) - Campus Laranjeiras do Sul, in response to the transformations triggered by the COVID-19 pandemic and the subsequent formal adoption of telecommuting. In light of this, this research aims to analyze the institutionalization of telecommuting at UFFS - Campus Laranjeiras do Sul. Drawing on Tolbert and Zucker's (1999) theoretical model of institutionalization processes as a foundation, this study employs a quantitative descriptive approach. The methodology involves the administration of a structured questionnaire to Administrative and Educational Technicians (TAEs) engaged in telecommuting roles. The questionnaire was designed to assess the stages of telecommuting institutionalization based on Tolbert and Zucker's (1999) theoretical model. Participants were invited to express their perceptions and experiences through responses on a Likert scale, addressing the constructs of habituation, objectivation, and sedimentation. A research sample was comprised of 72, who represented the target population at the Campus. However, the final sample for the research consisted of 47 participants, making it representative and significant. The main findings indicate that the sedimentation of telecommuting was perceived as the most advanced stage, with an average score of (3,87), followed by objectivation (3,70) and habituation (3,41). Most participants reported a positive perception of telecommuting, believing it contributed to improvements in UFFS's performance. Additionally, the low resistance to the continuation of telecommuting and the intention to continue working remotely were notable trends among respondents. These results provide a clearer understanding of the institutionalization of telecommuting at UFFS and how this mode of work has evolved within the institution. The findings of this study can serve as a foundation for enhancing telecommuting management at UFFS and influencing future decisions related to remote work. This study provides fundamental insights with significant practical, theoretical, and social implications. For UFFS managers and other academic institutions, the findings serve as a guide for the effective implementation of telecommuting. Furthermore, the results can influence policies and practices related to remote work. In a social context, the research can benefit STAE, increasing their confidence, motivation, and guiding efforts toward professional development in technology and innovation.